Taming the Female River: A Gendered Environmental History of the Chenab (Journal of Gender and Social Issues, 2025)
By situating it within the longstanding traditions of gendered and anthropomorphized understandings of rivers in South Asia, this article explores how local communities in Punjab viewed the River Chenab as a maada (female) river, owing to its fertility, fluidity, and unpredictable yet nurturing floods. Drawing on local and British archival sources, the article traces the heterogeneous and negotiated precolonial environmental relations around the Chenab. It explains how these were strained and altered under a colonial environmental transformation grounded in the ideas of productivity and hydraulic order. This article foregrounds the understudied role of river-training schemes in altering the Chenab’s morphology and seasonal rhythms and argues that environmental transformation of the Chenab led to a symbolic shift: the river, once perceived as a fertile and unpredictable female force, was reshaped into a regulated, mechanical system under the paternalistic Punjab administration and colonial hydraulic regime.
Keywords: Gendered ecological transformation; Colonial Hydrology; Environmental History; River Training; Punjab